The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1063/1.365049
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and strain relaxation in organometallic vapor phase epitaxy of strain-compensated GaInP/InAsP multilayers on InP(001)

Abstract: The various mechanisms responsible for the strain relaxation of strain-compensated GaInP/InAsP multilayers grown on InP(001) using low-pressure organometallic vapor-phase epitaxy (LP-OMVPE) were investigated using a combination of transmission electron microscopy (TEM), high-resolution x-ray diffraction (HRXRD), and reciprocal lattice mapping. We examined separately the effect of the misfit strain f as well as the total strain energy εT on the strain relaxation mechanisms. We also investigated the effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In summary, a comparison of The anisotropic thickness modulation mentioned above has already been reported for strain-compensated MQW structures of other material systems, such as InGaAs(P) and InAsP [15][16][17]. As in those previous studies, growth of the compressive-strained well layers is more favorable on locally thin regions of the tensile-strained barrier layer, and also the thickness modulation can be suppressed by decreasing the substrate temperature [18,19]. In contrast, for the other material systems, a compressive strain larger than 1.5% is usually required to induce the thickness modulation in the MQW region within a small number of periods [17,20].…”
Section: Methodssupporting
confidence: 63%
“…In summary, a comparison of The anisotropic thickness modulation mentioned above has already been reported for strain-compensated MQW structures of other material systems, such as InGaAs(P) and InAsP [15][16][17]. As in those previous studies, growth of the compressive-strained well layers is more favorable on locally thin regions of the tensile-strained barrier layer, and also the thickness modulation can be suppressed by decreasing the substrate temperature [18,19]. In contrast, for the other material systems, a compressive strain larger than 1.5% is usually required to induce the thickness modulation in the MQW region within a small number of periods [17,20].…”
Section: Methodssupporting
confidence: 63%
“…These values are slightly less than that measured for LM MQWs and may be explained by the reduced AlInAs barrier layer thickness in the SC MQWs. Thus, under the presently described growth conditions, there is no degradation in the atomic step structure of 1.5% SC MQWs, and the surface remains stable from the onset of growth until the end, with no indication of strain-induced surface modulation [22]. It is noted that the orientation of the steps shown in Fig.…”
Section: And 15% Gainas/alinas Sc Mqws and Sc Qcl Materials Resultsmentioning
confidence: 92%
“…Organometallic vapor phase epitaxy (OMVPE) was used for the growth of AlInAs/GaInAs/InP SC materials and QCLs with strain levels of 1 and 1.5%. In previous studies on growth of SC multiple-quantum-wells (MQWs) with compressive-GaInAs/tensile-GaInAs and GaInP/InAsP, it was reported that the photoluminescence and interfaces of SC MQWs degraded with increasing layer strain and increasing number of periods [20][21][22]. Those studies also showed that material quality could be improved by decreasing growth temperature, increasing V/III ratio, and minimizing or eliminating growth interruptions.…”
mentioning
confidence: 93%
“…[11][12][13][14]. Based on the microstructural characterization and d-spacing, it is believed that the surface protrusions are formed by surface undulation below a critical thickness.…”
Section: Resultsmentioning
confidence: 99%